2015
DOI: 10.2147/opth.s83552
|View full text |Cite
|
Sign up to set email alerts
|

Cataract surgery and methods of wound closure: a review

Abstract: Clear corneal incisions are routinely used in cataract surgery, but watertight wound closure may not always be achieved, which can increase the risk for anterior chamber fluid egress or ocular surface fluid ingress. A new US Food and Drug Administration-approved ocular sealant appears to have good efficacy in sealing clear corneal incisions; its use may be indicated when wound integrity is in question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 68 publications
(174 reference statements)
0
33
0
Order By: Relevance
“…While clear corneal incision offers a shorter procedure time, less astigmatism, and faster visual recovery, compared with a scleral tunnel procedure,25 wound integrity and fluid influx from self-sealing clear corneal incisions have been issues for a long time 2728. Also, whether suturing of the corneal wound in cataract surgery improves wound integrity has been debated 2930. The role of sutures in postoperative endophthalmitis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…While clear corneal incision offers a shorter procedure time, less astigmatism, and faster visual recovery, compared with a scleral tunnel procedure,25 wound integrity and fluid influx from self-sealing clear corneal incisions have been issues for a long time 2728. Also, whether suturing of the corneal wound in cataract surgery improves wound integrity has been debated 2930. The role of sutures in postoperative endophthalmitis is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, air injection is used for the reformation of the anterior chamber after phacoemulsification [ 12 ]. However, some studies reported air leakiness in 1/3 of the included cases [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods generally have significant drawbacks. For example, cyanoacrylate glue is associated with low biocompatibility, poor transparency, rough surface, difficult handling, and poor integration with corneal tissues ( 4 , 5 ). Grafting requires donor tissues, advanced surgical skills, and specialized equipment.…”
Section: Introductionmentioning
confidence: 99%